The application of diagnostic methods for disturbance of reading and writing in Russian population studies - George A. Karkashadze; Marina A. Kurakina; Leyla S. Namazova-Baranova; Elena A. Vishneva; Elena V. Kaytukova; Kamilla E. Efendieva; Tinatin Yu. Gogberashvili; Tatiana A. Salimgareeva; Safarbegim H. Sadilloeva; Tatiana A. Konstantinidi; Natalia E. Sergeeva; Julia E. Kazanceva; et al. (Педиатрическая фармакология, 2023)
Dyslexia (disturbance of reading) and dysgraphia (disturbance of writing) are a common problem of teaching children in secondary schools. Information on the prevalence of these conditions is ambiguous, the data presented in the Russian speech therapy literature differ from the results of a few foreign works, and therefore population studies are becoming particularly relevant. The review of the domestic methodological base with the prospect of application in population research and international approaches to population screening are presented.